A Study of DSN-MUI Fatwa No. 153/2022 concerning Discounts on Early Settlement of Murabahah Financing, - Ali Sajad; Ah. Azharuddin Lathif; Diana Mutia Habibaty (Al-Amwal : Journal of Islamic Economic Law, 2025)
Purpose - This study was conducted to clarify common misconceptions in understanding the distinction between the time value of money theory and the economic value of time theory in relation to DSN Fatwa No. 153/DSN-MUI/VI/2022 on the Early Settlement of Murabahah Financing, particularly with reference to the fiqih principle inna li al-zamani hisshotan min al-tsaman. Methods - This research constitutes a library study employing a normative approach in examining statutory regulations, scholarly books, classical fiqh works, DSN-MUI fatwas, and other relevant literature pertaining to the subject of this thesis. A descriptive analytical method was applied to elaborate on the central theme, providing an in-depth explanation based on the facts identified by the researcher. Results - The results of the research show that DSN’s Fatwa No. 153/DSN-MUI/VI/2022—specifically the fiqh principle inna li al-zamani hisshotan min al-tsaman—accommodates the theory of the economic value of time, rather than the time value of money. This conclusion is substantiated through a comparative analysis of several aspects shared between the economic value of time theory and the fiqih principle, namely: the role of money, the role of time, tangible assets/real effort, the distinction between cash and deferred prices, the practice of discounts, and the moral/maslahah dimension. Implications - As a practical implication, the results of this research can be used as a reference for the wider public and, more specifically, for financial practitioners, in order to avoid misinterpretations regarding the distinction between the time value of money and the economic value of time. Such understanding is essential to accurately identify which theory is accommodated within the fiqh maxim inna li al-zamani hisshotan min al-tsaman as reflected in DSN Fatwa No. 23/DSN-MUI/III/2002 on Discounts for Early Settlement of Murabahah Financing.